The sodium prevalence in carbonated soft drinks sold in Brazil - Nunes, Sandra Fernanda; Freire, Sonia Maria; Castel-Branco, Maria Margarida; Figueiredo, Isabel Vitória (Revista Gestão & Saúde, 2017)
The carbonated soft drinks intake has changed the children eating habits. This factor may be directly associated with arterial hypertension due the high consumption of sodium present in foods and drinks industrialized. This study was to compare sodium levels between two different types of carbonated soft drinks, carbonated sugar drinks and diet drinks to define what type of drink has the lowest sodium content and alerting healthcare professionals about the presence of sodium in industrialized beverages. The study included labels of carbonated soft drinks n = 33 ”“ sugar drinks (n = 21) or diet drinks (n = 12) ”“ of five different flavors.All carbonated soft drinks evaluated have sodium in its composition. However, the sodium presence in carbonated sugar drinks was significantly lower when compared with carbonated diet drinks (69.05 ± 16.55 vs. 145.30 ± 47.36mg Na/l, respectively).Studies to identify children's eating habits related with increased consumption of foods and drinks manufactured are needed to identify, reduce and prevent high blood pressure.